Lung Cancer in Oregon - John Hart (SAGE Publishing, 2011)
Factors thought to be related to lung cancer include smoking, radon, and educational attainment. These factors were analyzed in the present ecological study for Oregon with correlation and linear regression statistics. A moderate, inverse, and statistically significant correlation was found with educational attainment while surprisingly, negligible and statistically insignificant correlations were found with smoking and radon. More rigorous research such as case-control study designs, are indicated to verify or refute these findings.